1972
DOI: 10.1136/bmj.4.5839.520
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection and Renal Transplant Rejection

Abstract: had developed a duodenal ulcer, one a gastric ulcer, one a combined duodenal and gastric ulcer, and one was found to have radiological evidence of achalasia of the cardia. These patients were referred for surgical treatment, with excellent results in all except the patient with achalasia. Of the four remaining patients, further radiological investigation had shown renal disease in -two, but with no evidence of gastrointestinal disease, and two were again found to have no abnormality.When the radiological diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 7 publications
3
41
1
Order By: Relevance
“…47 How viral infections are involved in the development of chronic allograft nephropathy is not yet understood. We, as many other authors, [4][5][6][7][8][9] have observed that the number of acute rejections in renal transplanted patients with infections is higher than in patients who do not undergo infections. The occurrence of acute rejections is known as a risk factor for development of chronic allograft nephropathy.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…47 How viral infections are involved in the development of chronic allograft nephropathy is not yet understood. We, as many other authors, [4][5][6][7][8][9] have observed that the number of acute rejections in renal transplanted patients with infections is higher than in patients who do not undergo infections. The occurrence of acute rejections is known as a risk factor for development of chronic allograft nephropathy.…”
Section: Discussionsupporting
confidence: 52%
“…1 Active CMV infection is the most frequent infection in renal transplanted patients, 2,3 and it has been shown to be a risk factor for the occurrence of acute rejection episodes. [4][5][6][7][8][9] CMV infection induces activation and proliferation of B lymphocytes in mice as in humans. 10,11 In renal transplanted patients experiencing CMV infection, an early transient increase in peripheral B lymphocyte levels has been documented.…”
mentioning
confidence: 99%
“…Theoretical concerns have been raised regarding the potential for triggering allograft rejection with vaccination (1,(18)(19)(20)(21)(22) (23)(24)(25) …”
Section: Its Efficiency In Immunodepressed Individuals Remains a Comentioning
confidence: 99%
“…In addition to increased rates of lower respiratory infection with influenza, studies have also reported increased acute and chronic allograft rejection after infection, specifically in lung and kidney transplant recipients (1,(3)(4)(5). Therefore, SOT patients are recommended to receive the annual trivalent inactivated influenza vaccine (6,7).…”
Section: Introductionmentioning
confidence: 99%